Protective effects of dietary resveratrol supplementation against oxidative stress in diquat-challenged piglets. Issue 1 (14th December 2020) - Xun, Wenjuan; Fu, Qingyao; Hou, Guanyu; Shi, Liguang; Cao, Ting
Abstract: To evaluate the protective effects of dietary resveratrol (RES) supplementation against oxidative stress in piglets, a total of 30 weaned piglets (aged 28 + 2 d) were randomly divided into five treatments ( n  = 6): C group (basal diet), NC group (basal diet + diquat challenge), and basal diet containing either 10, 30, or 90 mg/kg of RES administered to piglets injected with diquat. The trail lasted 21 d. On day 15 after the initiation of treatment, piglets were intraperitoneally injected with 10 mg/kg body weight (BW) diquat or the same amount of saline. The feed intake and faecal consistency were recorded daily. Blood samples were collected for antioxidative, immune parameters and cytokines analysis. RES addition showed a negative tendency ( p  = .052) on faecal score during the pre-challenge period. Diquat challenge reduced the growth performance and induced oxidative stress and inflammatory responses of piglets ( p  < .05). However, the growth performance was improved, and faecal score was decreased in 90 mg/kg RES groups ( p  < .05). Compared with the NC group, addition of 90 mg/kg RES increased activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and total antioxidant capacity (T-AOC), and reduced malonaldehyde (MDA), cortisol and adrenocorticotropic hormone (ATCH) concentration ( p  < .05). Moreover, supplementation with 90 mg/kg RES increased serum concentration of interleukin-4 (IL-4) ( p  < .05) but decreased serum tumour necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β) ( p  < .05). In conclusion, the study indicated that RES showed overwhelming advantage in reducing diarrhoea and attenuating the oxidative stress of piglets challenged with diquat. Highlights: Dietary resveratrol supplementation improved growth performance and reduce diarrhoea of piglets challenged with diquat. The protective effects of dietary resveratrol supplementation against oxidative stress and inflammation in diquat-challenged piglets were confirmed. The experimental results provide theoretical and practical value for further research on the antioxidant mechanisms of resveratrol in weaned piglets.